Apakah Persepsi Mahasiswa penting dalam Karier Auditor?: Studi Pada Mahasiswa Program Studi Akuntansi Universitas Bhayangkara Jakarta Raya - Mukti, Aloysius Harry; Sari, Eka Lala; Handayani, Nur Tiara; Lestari, Rahmawati Indah; Amanda, Tiara Audia; Chahyani, Zahra Fauziah (Penerbit Goodwood, 2024)
Purpose: This study analyzes the perceptions that influence accounting students at Bhayangkara University Jakarta Raya in choosing a career as an auditor through several indicators. Methodology/Approach: The approach used was descriptive and quantitative. The sample in this study comprised 87 students from Bhayangkara University, Jakarta, Raya. Data were collected through questionnaires distributed to students using a purposive sampling method and processed using SPSS with classical assumptions and hypothesis testing. Results: The results indicate that financial rewards, professional training, professional recognition, and social value have negative and insignificant effects on accounting students’ interest in a career as an auditor. The work environment variable, market considerations, and personality have a positive and significant effect on accounting students’ interest in their career as an auditor. Limitations: (1) The number of samples that did not represent all populations must be carefully determined. (2). A normality test was performed using a scatter plot. Further research can utilize the Kolmogorov test so it can more precisely Contribution: This study contributes to several aspects (1). This was the first study to explore the intentions of students at Universitas Bhayangkara Jakarta Raya (2). This research elaborated the perception regarding auditor career.